Internet Information Services Administration - Adam, Kelli; Stanley, Lisa (Sams, 2000)
Administrators who know IIS from previous versions need this book to show them in concrete detail how to configure the new protocols, authenticate users with the new Certificate Server, and implement and manage the new e-commerce features. You want to know how to work with the MMC, so that you'll be ready for Windows NT 5.0. This book gives you all of that: a quick read that provides real world solutions, and doubles as a portable reference. Although IIS has been available for several years now, version 4.0 of the Internet Information Server marks a major change in Microsoft's approach to Enterprise Web Service. The brand new feature set in IIS 4.0 reads like a wish list of hot Internet technologies. Administration of IIS has been overhauled by the integration of the Microsoft Management Console and is the first product to use MMC.